2021
DOI: 10.1186/s10195-021-00603-w
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the MOCART score: a systematic review

Abstract: Background The present systematic review analysed the available literature to assess reliability of the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score in the evaluation of knee and ankle osteochondral lesions. Methods All the studies using the MOCART score for knee and/or talus chondral defects were accessed in March 2021. A multivariate analysis was performed to assess associations between the MOCART score at last follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Several studies analysed the magnetic resonance observation of cartilage repair tissue (MOCART) scoring system to evaluate the quality of the chondral regeneration. However, the MOCART score demonstrated no association with patient characteristics and with the surgical outcome in patients who underwent surgical management for knee and talus chondral defects 78 . The reviewers (F. M. and H. S.) who performed the literature search, data extraction, risk of bias assessment were the main authors of two of the included studies 39 , 40 .…”
Section: Discussionmentioning
confidence: 89%
“…Several studies analysed the magnetic resonance observation of cartilage repair tissue (MOCART) scoring system to evaluate the quality of the chondral regeneration. However, the MOCART score demonstrated no association with patient characteristics and with the surgical outcome in patients who underwent surgical management for knee and talus chondral defects 78 . The reviewers (F. M. and H. S.) who performed the literature search, data extraction, risk of bias assessment were the main authors of two of the included studies 39 , 40 .…”
Section: Discussionmentioning
confidence: 89%
“… 6 However, substantial controversy existed regarding the correlation between functional outcomes and MRI findings after repair for OLT. 34 A case series with 1-year follow-up found no correlation between MOCART score and patient-reported outcomes after repair of OLT. 1 In contrast, a previous study revealed that the MOCART score was in moderate association with functional outcomes at a mean of 3.6 years (range, 2.2-8.1 years) after microfracture.…”
Section: Discussionmentioning
confidence: 97%
“…Using an overall or composite MOCART score without reference to individual domains did not allow for interpretation of the degree of integration in many of the studies eligible for full-text screening. The evidence already suggests that MOCART scores might not correlate well with patient characteristics and surgical outcomes [ 30 ]. Therefore, if we are to understand how integration relates to improved clinical outcomes, future studies will have to consider integration independently.…”
Section: Discussionmentioning
confidence: 99%
“…For studies evaluating integration using MRI, the “integration to the border zone” component was extracted from scoring systems such as the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score, which post-operatively assesses cartilage repair in comparison to adjacent hyaline cartilage [ 30 , 31 ]. The results were sometimes presented as the proportion of patients achieving a predefined MOCART border integration score: (1) complete integration with adjacent cartilage; (2) incomplete integration (split like border visible); (3) a visible demarcating border of <50% of the length of the repair tissue; or (4) a visible defect >50% of the length of the repair tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation